2020
DOI: 10.3390/su12062549
|View full text |Cite
|
Sign up to set email alerts
|

Soil Quality and Heavy Metal Pollution Assessment of Iron Ore Mines in Nizna Slana (Slovakia)

Abstract: Mining activities have resulted in the existence of dumps, which generally present a perpetual danger of moving and transforming toxic elements. The experimental study was carried out in Nizna Slana (Slovakia) where the main source of emission was the iron-ore mining–processing factory focused on siderite mining. Siderit from Nizna Slana is highly ferrous with an increased level of the Mn content. Among the undesirable impurities on the deposit are mainly As, S, Pb, and Zn. According to the environmental regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 54 publications
3
30
0
Order By: Relevance
“…High concentrations of heavy metals in soils can damage ecosystems and consequently human health (Fazekašová and Fazekaš 2020). Therefore, methods of preventing and for restoring soils polluted with heavy metals are needed.…”
Section: Introductionmentioning
confidence: 99%
“…High concentrations of heavy metals in soils can damage ecosystems and consequently human health (Fazekašová and Fazekaš 2020). Therefore, methods of preventing and for restoring soils polluted with heavy metals are needed.…”
Section: Introductionmentioning
confidence: 99%
“…In this research it was noted that microbes inhabiting the topsoil environment on sites SG and MS, which had a relatively high lead content in the topsoil (A layer), were characterized by statistically signi cant lower microbial functional diversity index (H') and low metabolic activity (AWCD) (Table 4). The AWCD index provides information on the whole metabolic activity of microorganisms in the soil environment (Gomez et al 2004) and re ects metabolic pro les of the soil microbial community, which could be affected by such pollutants as heavy metals (Teng et al 2008, Fazekašová & Fazekaš 2020. In this research, a large variation of this parameter was found for the A layer between the analysed research plots (30.0-133.0 OD).…”
Section: Functional Diversity Of Soil Bacteria and Soil Respirationmentioning
confidence: 63%
“…This stunning amount of waste is partly because 99 % of the things we buy is trashed within six months. Dumping waste and improper waste management have negative consequences on the planet, such as (i) pollution of soil (waste can leak hazardous chemicals into the soil and, from there, into our food) [3,4], (ii) air pollution (the trash that is silicone, neoprene, natural rubber). In some cases, a cable may has metal shieldscalled armored cable (armors means mechanical protection that protects the cable from possible external aggressions: animals, physical damage, etc.…”
Section: Introductionmentioning
confidence: 99%